2021
DOI: 10.1210/jendso/bvab048.515
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2B, Open-Label, Dose-Ranging Study of Encaleret (CLTX-305) in Autosomal Dominant Hypocalcemia Type 1 (ADH1)

Abstract: Autosomal dominant hypocalcemia type 1 (ADH1) is a rare form of hypoparathyroidism caused by gain-of-function pathogenic variants in the gene encoding the calcium-sensing receptor (CaSR). It is characterized by variable degrees of hypocalcemia, hyperphosphatemia, and hypomagnesemia, with inappropriately low levels of parathyroid hormone (PTH) and hypercalciuria. Conventional therapy includes oral calcium and activated Vitamin D supplementation, which can lead to or exacerbate hypercalciuria. As a result, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Calcilytics have been studied as potential treatments for ADH1. ( 46 , 47 ) A proof‐of‐concept trial in patients with ADH1 using an intravenously infused calcilytic (NPSP795) demonstrated a dose‐dependent increase in blood PTH levels in patients with ADH1. ( 46 )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calcilytics have been studied as potential treatments for ADH1. ( 46 , 47 ) A proof‐of‐concept trial in patients with ADH1 using an intravenously infused calcilytic (NPSP795) demonstrated a dose‐dependent increase in blood PTH levels in patients with ADH1. ( 46 )…”
Section: Resultsmentioning
confidence: 99%
“…All supplemental calcium and activated vitamin D were discontinued before initiation of encaleret. ( 47 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, these mutations lead to mild hypocalcemia in humans and mice [25,34,35]. Recently, calcilytics were shown to reduce CaSR function by acting as negative allosteric modulators of this receptor thereby increasing PTH secretion and, importantly reducing urinary calcium excretion, in patients with ADH1 [36 ▪▪ ]. GNA11 mutations can also be associated with impaired growth [37], thus potentially pointing towards a role for this signaling protein in growth plate maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Encaleret is currently being studied in clinical research targeting autosomal dominant hypocalcemia type 1 (ADH1). In a phase 2 clinical trial involving adults with ADH1, encaleret corrected hypocalcemia, reduced hypercalciuria, and increased PTH secretion [6]. We previously reported that AXT914, another calcilytic, increased PTH secretion and corrected abnormal calcium and phosphorus homeostasis in rats with post-surgical hypoparathyroidism [7].…”
mentioning
confidence: 99%